Slow Release Nitrogen in Cassava Nutrition - Vinod G S (Department of Agronomy, College of Agriculture, 1988)
An investigation was undertaken at the College of Agriculture, Vellayani during the year 1985-86 to study the effect of slow-release nitrogen sources on cassava. The variety used for the trail was Sree Visakha. The treatments consisted of four sources namely urea, neemcake coated urea, urea super granule and rubber cake coated urea each at five levels of nitrogen (50, 75, 100, 125 and 150 kg/ha). The experiment was laid out in a 4 x 5 rectangular lattice design with three replications. Application of slow release sources of nitrogen like urea super granule and neem cake coated urea enhanced the growth characters of tapioca such as plant height, number of functional leaves, number of nodes and the leaf area index. Higher levels of nitrogen gave better results in the growth characters. The highest number of tubers, maximum tuber weight and the highest tuber yield were recorded by the urea super granule application, followed by neem cake coated urea. Among the levels of nitrogen tried, the level 150 kg/ha gave the highest yield. Starch content, crude protein content and the hydrocyanic acid contents were not affected by the slow-release source of nitrogen while higher levels of nitrogen application increased the hydrocyanic acid content and the crude protein content. Urea super granule recorded the highest nitrogen uptake and potassium uptake followed by neem cake coated urea. There was no significant difference in the total nitrogen content of the soil with the use of slor-release sources of nitrogen. The treatment combination of neem coated urea tried at 150 kg N/ha resulted in the maximum net return. Though urea super granule gave the maximum yield its cost of cultivation was higher than that of the other sources. So it is more economical to use neem cake coated urea than urea super granule. So in general, the slow-release sources of nitrogn like urea super granule and neem cake coated urea resulted in a better performance than prilled urea.